2016
DOI: 10.1080/10428194.2016.1239259
|View full text |Cite
|
Sign up to set email alerts
|

The CDK inhibitor AT7519M in patients with relapsed or refractory chronic lymphocytic leukemia (CLL) and mantle cell lymphoma. A Phase II study of the Canadian Cancer Trials Group

Abstract: AT7519M is a small molecule inhibitor of cyclin-dependent kinases 1, 2, 4, 5, and 9 with in vitro activity against lymphoid malignancies. In two concurrent Phase II trials, we evaluated AT7519M in relapsed or refractory chronic lymphocytic leukemia (CLL) and mantle cell lymphoma (MCL) using the recommended Phase II dosing of 27 mg/m twice weekly for 2 of every 3 weeks. Primary objective was objective response rate (ORR). Nineteen patients were accrued (7 CLL, 12 MCL). Four CLL patients achieved stable disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…AT7519 is a pan-CDK inhibitor that likewise caused G2/M arrest and decreased GSK3b ser9 phosphorylation. Multiple phase II clinical trials have been completed but, although treatment is well tolerated, low response rates were observed (Seftel et al, 2017). Therefore, ABC1183 represents a novel molecule for selectively inhibiting CDK9 and GSK3.…”
Section: Discussionmentioning
confidence: 99%
“…AT7519 is a pan-CDK inhibitor that likewise caused G2/M arrest and decreased GSK3b ser9 phosphorylation. Multiple phase II clinical trials have been completed but, although treatment is well tolerated, low response rates were observed (Seftel et al, 2017). Therefore, ABC1183 represents a novel molecule for selectively inhibiting CDK9 and GSK3.…”
Section: Discussionmentioning
confidence: 99%
“…However, compound 4 exhibited weaker inhibitory activity against CDK-2 (IC 50 ¼ 47 nM) compared to the parent compound 3 which indicates that the aromatic 4-fluorophenyl moiety is favoured for CDKs inhibition 16 , Figure 1. Mechanistic study of compound 4 also revealed high inhibitory activity against CDK-9, while weaker activity was observed against CDKs 1, 3, 4, and 6 17 . Moreover, replacement of the 4-piperidinyl ring in compound 4 by the N-4-((2aminophenyl)carbamoyl)benzyl moiety afforded compound 5 with higher inhibitory activities against CDK-1/2 18 .…”
Section: Introductionmentioning
confidence: 93%
“…Based on the above-mentioned data, the current study was performed to optimise the cytotoxic potential, study the structureactivity relationship (SAR), and investigate the mechanism of action of the pyrrolizine-5-carboxamide 10. In this study, scaffold A ( Figure 3) was designed bearing the pharmacophoric groups of the lead compound 10 and the multi-CDKIs 3 17 . In addition, a small library of 1302 urea/thiourea derivatives was generated through different structural modifications in scaffold A, Supplementary data ( Figures S1-S42).…”
Section: Rationale and Designmentioning
confidence: 99%
See 2 more Smart Citations